Polyyne-producing Burkholderia suppress Globisporangium ultimum damping-off disease of Pisum sativum (pea) - Webster, Gordon; Mullins, Alex J.; Petrova, Yoana D.; Mahenthiralingam, Eshwar (Frontiers in Microbiology, 2023)
Extensive crop losses are caused by oomycete and fungal damping-off diseases. Agriculture relies heavily on chemical pesticides to control disease, but due to safety concerns multiple agents have been withdrawn. Burkholderia were successfully used as commercial biopesticides because of their fungicidal activity and plant protective traits. However, their potential for opportunistic pathogenicity led to a moratorium on their registration as biopesticides.Subsequently, Burkholderia were shown to produce multiple specialised metabolites including potent antimicrobial polyynes. Cepacin A, a polyyne produced by Burkholderia ambifaria biopesticide strains was shown to be an important metabolite for the protection of germinating peas against Globisporangium ultimum (formerly Pythium) damping-off disease. Recently, there has been an expansion bacterial polyyne discovery, with the metabolites and their biosynthetic gene pathways found in several bacterial genera including Burkholderia, Collimonas, Trinickia, and Pseudomonas. To define the efficacy of these bacterial polyyne producers as biopesticidal agents, we systematically evaluated metabolite production, in vitro microbial antagonism, and G. ultimum biocontrol across a panel of 30 strains representing four bacterial genera. In vitro polyyne production and antimicrobial activity was demonstrated for most strains, but only Burkholderia polyyne producers were protective within the in vivo G. ultimum damping-off pea protection model. B. ambifaria was the most effective cepacin-expressing biopesticide, and despite their known potential for plant pathogenicity Burkholderia gladioli and Burkholderia plantarii were uniquely shown to be protective as caryoynencin-producing biopesticides. In summary, Burkholderia are effective biopesticides due to their suite of antimicrobials, but the ability to deploy polyyne metabolites, caryoynencin and cepacin, is strain and species dependent.